Reproductive and child health: contraceptive knowledge, use and factors affecting contraceptive use among female adolescents (15 – 19 years) in Ghana - Darko, Justina Asieduaa (2016)
A thesis submitted to The Department of Economics Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the degree of Master of Science,